THE ROLE OF AI-DRIVEN PERSONALIZATION IN SHAPING CONSUMER LOYALTY IN E-COMMERCE - Sucidha, Irma (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Digital transformation has driven the adoption of artificial intelligence (AI) technology in e-commerce personalization strategies, which has the potential to increase consumer loyalty. However, understanding of how AI-driven personalization affects consumer loyalty is still limited. This study aims to explore the influence of AI-driven personalization on consumer loyalty in e-commerce platforms, as well as identify the psychological mechanisms involved. The approach used is a Systematic Literature Review (SLR) by collecting and analyzing 28 peer-reviewed articles from the Scopus and Web of Science databases. Data were analyzed using thematic coding techniques and the Stimulus-Organism-Response (S-O-R) framework to understand the relationship between AI personalization and consumer loyalty. The findings indicate that AI-driven personalization significantly increases consumer loyalty through mediators such as trust, perceived value, and satisfaction. In addition, moderating factors such as privacy concerns and product types also affect the effectiveness of personalization strategies. This study provides important insights for e-commerce practitioners in designing effective and ethical personalization strategies, and contributes to the development of consumer loyalty theory in the digital context.